Influence of Lining Design Parameters on the Greenhouse Gas Emissions of Chinese Highway Tunnel Construction. Issue 11 (November 2021) - Xu, Jianfeng; Dong, Chen; Guo, Dongming; Guo, Chun
To realize low-carbon design for tunnel construction, the authors explored the relationship between tunnel design and greenhouse gas (GHG) emissions. This study proposed typical design models of Chinese highway tunnels based on the lining design specifications and engineering design cases. The research modified the GHG emission calculation method based on the standard quota system. The marginal GHG emissions caused by a change of design parameters of tunnel lining were determined. The results show that the emissions from shotcrete, concrete arch wall, system bolts, and steel frames are sensitive to the change of design parameters, while steel mesh is not. As the design thickness increases, the emissions of the concrete arch wall, inverted arch, and shotcrete increase approximately linearly. The emission distributions of system bolts and steel frames under different spacing are given. Under the same longitudinal spacing condition, the emission ratio of I18 and I16 steel frames is 1.197, and that of I16 and I14 steel frames is 1.316. By defining the marginal emissions caused by the change of design parameters, this study carried out basic work for highway tunnel low-carbon designs. The research is of strategic significance for achieving energy conservation and emission reduction in the tunnel industry.